A Systematic Review of Current Applications of Fecal Microbiota Transplantation in Horses - Maimaiti Tuniyazi; Wenqing Wang; Naisheng Zhang (Veterinary Sciences, 2023)
Fecal microbiota transplantation (FMT) is a technique involving transferring fecal matter from a healthy donor to a recipient, with the goal of reinstating a healthy microbiome in the recipient’s gut. FMT has been used in horses to manage various gastrointestinal disorders, such as colitis and diarrhea. To evaluate the current literature on the use of FMT in horses, including its efficacy, safety, and potential applications, the authors conducted an extensive search of several databases, including PubMed, MEDLINE, Web of Science, and Google Scholar, published up to 11 January 2023. The authors identified seven studies that met their inclusion criteria, all of which investigated the FMT application as a treatment for gastrointestinal disorders such as colitis and diarrhea. The authors demonstrated that FMT was generally effective in treating these conditions. However, the authors noted that the quality of the studies was generally suboptimal and characterized by small sample sizes and a lack of control groups. The authors concluded that FMT is a promising treatment option for certain gastrointestinal disorders in horses. Nevertheless, more research is required to determine the optimal donor selection, dosing, and administration protocols, as well as the long-term safety and efficacy of FMT in horses.